Strategies to get published in high-impact journals - Ichwan, Solachuddin J. A. (2018)
Scientific and clinical researches have to be made accessible to other professionals and as broad of an audience as possible. Publishing in peer-reviewed journals is a way to disseminate and communicate the scientific discoveries to the greater scientific community. Scientific articles that have high impact are highly readable and the result of a collective and often synergistic effort. Nevertheless, many clinicians and scientists worldwide aim of publishing their research in high-impact journals as a requirement to improve both academic reputation and future career prospects. Preparing scientific manuscripts for publication in reputable academic journals is a highly competitive activity and often, daunting task. This brief review highlights important strategies for high-impact research and offers suggestions for achieving success when writing and submitting manuscripts to reputable journals.